Gambaran Proses Pembuatan Dan Penggunaan Transfemoral Prostesis Eksoskeletal Untuk Amputasi Atas Lutut Karena Kecelakaan Kerja - Nur Rachmat; Siska Meiwijayasmi (Interest : Jurnal Ilmu Kesehatan, 2019)
Background: Transfemoral exoskeletal prosthesis is an isntrument intervene in the form of a prosthesis fitted outside of the body that reverses the lower limb and can replace anatomical and functional functions. It is expected to provide satisfaction of amputee patient due work related accident. Methods: qualitative type with research methods used, namely interviews and observations. Results: manufacturing process of transdemoral exoskeletal prosthesis includes assessment, measurement, casting, fabrication, fitting, finishing. Conclusions: based of obsevations, interviews and analyzes carried out on tranfemoral prosthesis users, patiens now feel pious and happy to have progress in living activities using a prosthesis.